Organizational and technological aspects of environmental influences on business operations - Karpyuk, A. (Ways to Improve Construction Efficiency, 2015)
This paper investigates the environmental factors that affect the efficiency of enterprise management. We consider the classification of groups of factors affecting the management of the enterprise. Determined algorithm sequence analysis of the external environment with which you can set the desired list of areas making up the procedures and indicators for evaluating the effectiveness of management.